An Economic Integration Zone for the East African Community : Exploiting Regional Potential and Addressing Commitment Challenges - Dobronogov, Anton (2012)
Integration in the East African Community offers significant opportunities not only to expand trade among member states, but more importantly to scale up regional production to take advantage of much larger global market opportunities. Special economic zones are a potentially valuable instrument to facilitate the integration of regional value chains in support of this scaling up. They also have the potential to deliver powerful demonstration effects on the benefits of integration and to help entrench the integration process. This paper discusses the proposal for developing an "economic integration zone" in the East African Community. The benefits of such a zone could be substantial, as would be the practical challenges to implementation -- in particular the political economy challenges. However, a number of institutional and commercial solutions exist to address these challenges.